An introduction to surface energy driven growth nanoparticle synthesis and the development of single TiO₂ nanowire devices as memristors - O'Kelly, Curtis (Trinity College (Dublin, Ireland). School of Chemistry, 2015)
In this thesis aspects of a novel nanoparticle synthesis method and a unique multi-level resistance switching memory device are introduced. The dichotomy of the two programmes is addressed and a rationale for the transition between the projects is presented based on practical instrumental and material limitations. The nanoparticle synthesis method referred to as the surface energy driven growth (SEDG) is introduced and its physical principles explained. The SEDG method is especially suited for producing single-crystal metallic nanowires that cannot be produced via the similar vapour-solid-liquid method. The method has various applications in new nanomaterial discovery, binary alloy phase diagram dynamics and real time crystal growth kinetics.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin